ANALISIS KADAR AMILOID BETA PLASMA DENGAN GANGGUAN KOGNITIF PADA DIABETES MELITUS TIPE 2 - Syafrita, Yuliarni; Amir, Darwin; Decroli, Eva; Susanti, Restu (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2018)
Ã‚Â Ã‚Â Ã‚Â ANALYSIS OF PLASMA LEVELS OF BETA AMYLOID WITH COGNITIVE IMPAIRMENT IN TYPE 2 DIABETES MELLITUSABSTRACTIntroduction:Ã‚Â Type 2 diabetes mellitus (T2DM) and AlzheimerÃ¢â‚¬â„¢s disease are two kind of neurodegenerative disease that related with age. Patients with DM show a tendency to develop AlzheimerÃ¢â‚¬â„¢s disease, but there is no single marker for predicting a DM case will develop into AlzheimerÃ¢â‚¬â„¢s disease. Amyloid cascade beta disturbance is one factor involved in the pathogenesis of DM disease as well as in AlzheimerÃ¢â‚¬â„¢s disease, and still believed to be the main factor causing AlzheimerÃ¢â‚¬â„¢s dementia.Aims:Ã‚Â This research was aimed to determine the correlation between beta amyloid plasm level and demographic factors with the occurrence of cognitive dysfunction in type 2 diabetes mellitus patients.Methods:Ã‚Â This was a cross-sectional design study on patients with DM in special DM clinic at M Djamil and Ibnu Sina hospital, Padang, between AugustÃ¢â‚¬â€October 2016. Cognitive function was examined using the Montreal Cognitive Assessment Indonesian version (MoCA-Ina). Beta amyloid level was measured by enzyme-linked immunosorbent assay (ELISA) technique. Beta amyloid diagnostic ability was analyzed by using receiver operating characteristics (ROC). The correlation between the variables were analyze by using Chi-square, and p value p<0.05 was considered to be significant. To determine the strongest variables which correlated to cognitive dysfunction, logistic regression analysis were performed.Result:Ã‚Â 65 subjects included in this study, where cognititve dysfuntion were present in 35 patients (58.3%). There were significant correlation between disease duration and low levels of 42 beta amyloid in plasma (AÃŽÂ²42) with the occur- rence of cognitive dysfunction. The multivariate analysis showed that the disease duration, followed by low levels of AÃŽÂ²42 and education level were the variables correlated with cognitive dysfunction.Discussion:Ã‚Â There were a correlation between low levels of 42 beta amyloid in plasma with the occurrence of cog- nitive dysfunction in type 2 diabetes mellitus patients.Keywords:Ã‚Â Beta amyloid, cognitive impairment, demographic factors, type 2 DMABSTRAKPendahuluan:Ã‚Â Penyakit diabetes melitus tipe 2 (DM) dan penyakit Alzheimer adalah dua penyakit neurodegeneratif yang sering berhubungan dengan usia. Pasien dengan DM menunjukkan kecenderungan untuk menderita penyakit Alzheimer, namun belum ada satupun penanda untuk memprediksi kasus DM yang akan berkembang menjadi penyakit Alzheimer. Gangguan kaskade amiloid beta merupakan faktor yang terlibat pada patogenesis penyakit DM maupun pada penyakit Alzheimer, dan sampai sekarang masih dipercaya sebagai faktor utama yang menyebabkan demensia Alzheimer.Tujuan:Ã‚Â Mengetahui hubungan kadar amiloid beta plasma dan faktor demografi dengan gangguan fungsi kognitif pada penderita DM.Metode:Ã‚Â Penelitian dengan desain potong lintang ini, terhadap pasien DM yang berobat di Poliklinik khusus diabetes RSUP Dr. M Djamil dan RS Islam Ibnu Sina, Padang, pada periode AgustusÃ¢â‚¬â€œOktober 2016. Penilaian gangguan kognitif menggunakanÃ‚Â Montreal Cognitive AssesmentÃ‚Â versi Indonesia (MoCA-Ina), dinyatakan terganggu jika nilai <26.Kadar amiloid beta diperiksa dengan metodeÃ‚Â enzyme-linked immunosorbent assayÃ‚Â (ELISA) dan kemampuan diagnostik amiloid beta dianalisis denganÃ‚Â receiver operating characteristicsÃ‚Â (ROC). Hubungan antar variabel diuji denganÃ‚Â Chi- square, dikatakan bermakna bila nilai pÃ¢â€°Â¤0,05. Dilakukan analisis regresi logistik untuk menentukan variabel yang paling kuat hubungannya dengan gangguan fungsi kognitif.Hasil:Ã‚Â Didapatkan 65 subjek dengan rerata usia 61,62+7,6 tahun dan sebanyak 53,8% mengalami gangguan fungsi kognitif. Didapatkan hubungan yang bermakna antara lama sakit dan rendahnya kadar AÃŽÂ²42 plasma dengan terjadinya gangguan kognitif. Pada analisis multivariat diketahui bahwa urutan kekuatan variabel yang berhubungan dengan terjadinya gangguan fungsi kognitif adalah lama sakit, rendahnya kadar AÃŽÂ²42 plasma, dan tingkat pendidikan.Diskusi:Ã‚Â Terdapat hubungan antara lama sakit dan rendahnya kadar AÃŽÂ²42 plasma dengan terjadinya gangguan kognitif pada penderita DM.Kata kunci:Ã‚Â Amiloid beta,Ã‚Â DM tipe 2,Ã‚Â faktor demografi, gangguan kognitif